The value of electroencephalography in the diagnosis and prognosis of the likely outcomes hypoxic-ischemic brain lesions in term neonates - L. A. Krivtsova; V. V. Belsky (Бюллетень сибирской медицины)
In practice it’s often observed the discrepancy between clinical presentation of cerebral lesions in neonates and results of instrumental studies (neurosonography and computer tomography). The aim of the research was to explore the possibilities of the method of EEG for diagnosis and prognosis of cerebral lesions in neonates. The study was carried out in the design of Longitudinal prospective cohort controlled comparative non-randomized study with a simple glare. The study results demonstrate a great diagnostic and prognostic value of the method of EEG in detecting cerebral ischemia in neonates.